The distribution and density of Tapanuli orangutans (Pongo tapanuliensis) at potential corridor locations between forest fragments in Batang Toru, North Sumatra, Indonesia - ARFAH NASUTION; DYAH PERWITASARI-FARAJALLAH; S. SUCI UTAMI-ATMOKO (Society for Indonesian Biodiversity, 2020)
Abstract. Nasution A, Perwitasari-Farajallah D, Utami-Atmoko SS. 2020. The distribution and density of Tapanuli orangutans (Pongo tapanuliensis) at potential corridor locations between forest fragments in Batang Toru, North Sumatra, Indonesia. Biodiversitas 21: 5382-5388. The newly discovered Tapanuli orangutan (Pongo tapanuliensis) is in danger of being lost in a few decades due to their small population number in fragmented forest of Batang Toru. The major threats faced by this critically endangered ape, including: hunting, habitat loss, and fragmentation due to large infrastructure development and other developments in the key corridor area. The establishment of corridor and buffer zone is one such effort to maintain their population and bring them from the brink of extinction. Data on the population and distribution are needed to assess and provide baseline information for investigating the habitat condition of potential corridors and buffer zones. This study aimed to analyze population and distribution of Tapanui orangutan (Pongo tapanuliensis) in buffer zone and potential corridor of Batang Toru. Our study provides an initial dataset prior to the development of the hydrodam, which is important to understand the future post-development impact. The study was carried out in disturbed (Hutaimbaru and Bulu Mario) and undisturbed forest (Sitandiang and Hopong) of Batang Toru from June 2015 until February 2016. Orangutan nest, fig (Ficus spp.), and trees bearing fruit were recorded using a line transect method. This research showed that population and distribution of orangutan were influenced by forest conditions, threat level, and fruit availability. There were fewer nests per km2 in disturbed forest than in undisturbed forest, resulting in an orangutan density estimation to be 0.24 ind/km2, 0.14 ind/ km2 (Hutaimbaru and Bulu Mario) and 0.74 ind/km2, 0.36 ind/km2 (Sitandiang and Hopong). Number of nest in transects was influenced by the availability of fig class I and class II, but not fruit tree. The APL forest of Sitandiang is key area to connect the three populations of Tapanuli orangutan: east Batang Toru, west Batang Toru, and Sibualbuali. Furthermore, orangutan’s nests were encountered both in protected and non-protected forest, thus protection of such areas, especially areas including primary forest that harbor orangutan is essential for their long term survival. The conservation measures and action Tapanuli orangutan is alarming, thus we recommend all remaining habitat should be officially and strictly protected and collaboration work with multi-stakeholder is essential to establish the corridor as well as the strategic management plan of Tapanuli orangutan.